Two‐piece zirconia implants supporting all‐ceramic crowns: Six‐year results of a prospective cohort study. Issue 6 (6th April 2021) - Cionca, Norbert; Hashim, Dena; Mombelli, Andrea
Abstract: Objectives: The aim of this prospective clinical trial was to present the 6‐year outcomes of a two‐piece yttria‐stabilized tetragonal zirconia polycrystals (Y‐TZP) implant system in partially edentulous patients. Material and methods: Forty‐nine two‐piece zirconia implants were placed in 32 patients systemically healthy. Zirconia abutments were connected with adhesive resin cement. Single‐unit full‐ceramic crowns were cemented. The cases have been followed for an average of 82.2 ± 5.86 months after loading (range 74.93–92.26 months). Results: 24 participants with 39 implants were available for examination 6 years after loading. The cumulative implant survival rate was 83%. On an implant level, the cumulative mechanical complication rate was 17.5%, the cumulative technical complication rate was 13%, and the biological complication rate was 8%. After 6 years, subjects reported good satisfaction with the treatment: 3.7 ± 4.4 on a visual analog scale (VAS) from 0 to 100 mm. Conclusions: Within the limitations of this prospective case series study, two‐piece zirconia implants could offer an alternative for treatment of single edentulous spaces in the posterior region. The major complication on the long term of this pioneering system was the abutment fracture; however, due to the versatility of a two‐piece implant system, replacement of the broken parts was possible.